Pola Sosialisasi Penyuluh Agama Islam dalam Pencegahan Paham Radikalisme - Wahyu Ziaulhaq (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study tries to explain the socialization pattern of Islamic religious educators in preventing radicalism. The purpose of this study is to educate readers that radicalism is very dangerous to the integrity of the Unitary State of the Republic of Indonesia and must be prevented as early as possible. The practice of socializing Islamic religious instructors carried out in a persuasive and humanistic manner using religious languages ​​by always prioritizing the values ​​of tolerance. This research is a qualitative research with a descriptive approach. Data collection techniques used are observation and structured interviews. The results of this study are: First, Islamic religious instructors conduct early detection in all remote villages. Second, instilling in the community the principle of religious moderation in order to create a harmonious, harmonious and peaceful religious life. Third, convey to the public that there is no place for radical sects in the Unitary State of the Republic of Indonesia.